Composite with Silver Nanoparticles and Oregano Essential Oil-loaded Nanoparticles Intended for Wound Healing - Hernández-Rizo, Laura; Villanueva-Martínez, Angélica; Salas-Téllez, Enrique; del Carmen Camacho-Enríquez, Brígida; Vargas-Martínez, María Gabriela; Ganem-Rondero, Adriana (Pharmaceutical Nanotechnology, 2025)
PurposeSince wounds are a primary source of infection, it is desirable to have a wound dressing that prevents infectious processes during the tissue regeneration phase. In this regard, silver nanoparticles, oregano essential oil, and chitosan have been utilized due to their antimicrobial activity. This work focused on the preparation of a composite containing these three components, intended to provide protection for wounds, especially by exerting antimicrobial effects.MethodsA composite based on chitosan nanoparticles loaded with oregano essential oil (OEO) and silver nanoparticles was fabricated through the casting-solvent evaporation method. The films were prepared from a suspension of chitosan nanoparticles. The nanoparticles were characterized by size and entrapment efficiency. The surface of the films was observed by SEM, and the mechanical resistance, occlusive capacity, and antimicrobial activity against S. aureus, E. coli, and P. aeruginosa were evaluated. The release of OEO from the films was studied using Franz-type cells.ResultsA composite was successfully prepared from a dispersion of OEO-loaded chitosan nanoparticles (147.8 nm, PDI = 0.35; entrapment efficiency = 80.9%; loading capacity = 38%) and silver nanoparticles (19.6 nm, PDI = 0.4). A film could be formed that made the composite by pouring the chitosan nanoparticle dispersion directly into molds. The composite presented advantageous characteristics, such as being semi-occlusive (occlusion factor 40% and reduction in TEWL of 18%), allowing the sustained release of OEO (about 0.2 mgcm-2h-1 during 8 h), and having antimicrobial activity for the three strains evaluated.ConclusionThe prepared composite can be considered a potential candidate for dressing materials intended to prevent and treat wound infections.
Keywords: chitosan